Exploring Students’ Metacognitive Skills Through Learning Styles in a “Simple Pendulum” Experiment - Pertiwi, Faninda Novika; Kitthawee, Udomsak (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
Metacognitive ability refers to a student's awareness and understanding of their own cognitive processes, which can be enhanced by adopting an appropriate learning style. This study aimed to examine the metacognitive ability levels of students with different learning styles in a basic physics experiment course, specifically focusing on the topic of a simple pendulum. A quantitative descriptive research method was employed. Data were collected from 15 students (5 from each learning style group) using a validated and reliable questionnaire. The results indicated that auditory learners predominantly exhibited Tacit Use and Tacid Use levels, with one student at the Reflective Use level; visual learners demonstrated a range from Tacit Use to Strategic Use; and kinesthetic learners showed levels from Tacit Use to Reflective Use. In terms of metacognitive indicators, students across all learning styles exhibited moderate to high abilities in declarative, procedural, and conditional knowledge. Overall, following the simple pendulum experiment, students demonstrated moderate to high levels of metacognitive ability, reflecting a solid understanding of the experimental process and data collection related to gravitational acceleration. Notably, students with auditory, visual, and kinesthetic learning styles exhibited varying levels of metacognitive ability, which were not confined to a specific level. Additionally, students with lower basic physics scores generally demonstrated lower metacognitive ability (Tacit Use). Despite their diverse learning styles, students with low physics scores and low metacognitive abilities require a gradual, reflective, and structured approach to enhance their awareness and critical thinking skills.